2020
DOI: 10.1002/adma.201907880
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Based Plasmonic Heterogeneous Nanostructures: Building, Optical Responses, and Bioapplications

Abstract: The integration of multiple functional nanoparticles into a specific architecture allows the precise manipulation of light for coherent electron oscillations. Plasmonic metals-based heterogeneous nanostructures are fabricated by using DNA as templates. This comprehensive review provides an overview of the controllable synthesis and self-assembly of heterogeneous nanostructures, and analyzes the effects of structural parameters on the regulation of optical responses. The potential applications and challenges of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 84 publications
(249 reference statements)
0
23
0
Order By: Relevance
“…These DNA-based experiments can further explore molecule-based electronics and new biosensing platforms, because the DNA strand provides a versatile platform for interactions between ions, proteins, and other molecules within the photo-assisted transport junction. [12,119,156] As previously described, the plasmon resonance wavelength is affected by the gap conductance, molecule size, local refractive index, and charge transfer behavior within junctions. However, one study, published in 2019 by Readman et al, suggested the opposite plasmon resonance behavior to that previously found; [157] they identified anomalously large spectral shifts with subatomic resolution, using a lanthanide (Ln = Sm, Tb, Er, Lu) ion with two conjugated phthalocyanine (Pc) molecules.…”
Section: Aliphatic and Conjugated Molecule Gapmentioning
confidence: 86%
“…These DNA-based experiments can further explore molecule-based electronics and new biosensing platforms, because the DNA strand provides a versatile platform for interactions between ions, proteins, and other molecules within the photo-assisted transport junction. [12,119,156] As previously described, the plasmon resonance wavelength is affected by the gap conductance, molecule size, local refractive index, and charge transfer behavior within junctions. However, one study, published in 2019 by Readman et al, suggested the opposite plasmon resonance behavior to that previously found; [157] they identified anomalously large spectral shifts with subatomic resolution, using a lanthanide (Ln = Sm, Tb, Er, Lu) ion with two conjugated phthalocyanine (Pc) molecules.…”
Section: Aliphatic and Conjugated Molecule Gapmentioning
confidence: 86%
“…Nevertheless, there remains much to learn about these systems using, for example, in situ characterization, precise control, mass production, mechanism exploration, and functional application of noble‐metal composites. On the other hand, the versatile design of noble‐metal composites allows them to be used in other interesting emerging fields, covering electromagnetic interference (EMI) shielding, [ 285–287 ] printing, [ 288–291 ] biotechnology, [ 292–294 ] sensors, [ 295–298 ] and solar energy. [ 299–301 ] Based on the unique features of noble‐metal composites, combined with their finely tuned component and structure design, noble‐metal composites can be produced at low cost and in batches, which further promotes their application in the fields of optics, catalysis, medicine, and electricity.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticle assembly on pre-formed chiral templates. Conventional templates for chiral plasmonic assemblies include thin films patterned by e-beam-lithography, 118 polymers, 119,120 nanofibers, 121,122 DNA 98,[123][124][125][126][127][128][129] and other biomolecules. 130,131 For example, chiral assemblies have been synthesized in aqueous suspensions of plasmonic nanorods using chiral supramolecular nanofibers as templates (Fig.…”
Section: Chiral Nanostructures Obtained By Wet Chemistrymentioning
confidence: 99%